Iqbal’s Quest for Synthesis: Intertextual Negotiations of Selfhood in Western, Islamic, and Hindu Traditions - Jamil, Babar (Journal of Islamic and Religious Studies, 2025)
This article examines Muhammad Iqbal’s ambitious yet ultimately strained attempt to synthesize three major philosophical and religious traditions—modern Western thought, Islamic Sufism, and Hindu metaphysics—into a coherent vision of selfhood. Through a close reading of Iqbal’s major works, including Asrar-i-Khudi, Ramooz-i-Bekhudi, and The Reconstruction of Religious Thought in Islam, the paper argues that Iqbal’s project, though courageous and creative, remains internally unstable. The modern Western and Hindu traditions both affirm human autonomy and liberation often without reference to a transcendent God, while Islamic metaphysics grounds human dignity in servanthood before the Divine. Iqbal’s valorization of Khudi, his rejection of traditional Sufi "technologies of the self," and his politicization of mystical concepts reflect the profound pressures of postcolonial identity formation. Using insights from intertextuality theory and Michel Foucault’s analyses of spiritual technologies, the article shows how Iqbal’s reconstruction navigated but also internalized the contradictions of modernity. His struggle reveals both the possibilities and the tragic limitations faced by Muslim intellectuals seeking to renew tradition amidst historical dislocation. Rather than a final synthesis, Iqbal’s work remains an open invitation to reconsider the complex dynamics between tradition, freedom, and authenticity in the modern world.